10(.5x+2)-5=3(x-6)+1

Simple and best practice solution for 10(.5x+2)-5=3(x-6)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(.5x+2)-5=3(x-6)+1 equation:


Simplifying
10(0.5x + 2) + -5 = 3(x + -6) + 1

Reorder the terms:
10(2 + 0.5x) + -5 = 3(x + -6) + 1
(2 * 10 + 0.5x * 10) + -5 = 3(x + -6) + 1
(20 + 5x) + -5 = 3(x + -6) + 1

Reorder the terms:
20 + -5 + 5x = 3(x + -6) + 1

Combine like terms: 20 + -5 = 15
15 + 5x = 3(x + -6) + 1

Reorder the terms:
15 + 5x = 3(-6 + x) + 1
15 + 5x = (-6 * 3 + x * 3) + 1
15 + 5x = (-18 + 3x) + 1

Reorder the terms:
15 + 5x = -18 + 1 + 3x

Combine like terms: -18 + 1 = -17
15 + 5x = -17 + 3x

Solving
15 + 5x = -17 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
15 + 5x + -3x = -17 + 3x + -3x

Combine like terms: 5x + -3x = 2x
15 + 2x = -17 + 3x + -3x

Combine like terms: 3x + -3x = 0
15 + 2x = -17 + 0
15 + 2x = -17

Add '-15' to each side of the equation.
15 + -15 + 2x = -17 + -15

Combine like terms: 15 + -15 = 0
0 + 2x = -17 + -15
2x = -17 + -15

Combine like terms: -17 + -15 = -32
2x = -32

Divide each side by '2'.
x = -16

Simplifying
x = -16

See similar equations:

| 14+3(6x-9)+12x=101 | | 6(7-2)= | | m*6=12 | | -6.5(2t+4)-1.2(4t-6)= | | 5f/10=f+2/6 | | g(x)=-2x^2-12x-14 | | g+-91=-75 | | 2x^2+18=54 | | 374=95x+75x | | n-8= 5 | | 2(5x-5)-6(x+8)=21 | | p+12p=-5 | | 2(3p+1)=8(4+p) | | 3=12-3r | | 31=z-12 | | 31=z-12 | | 204=90x+80x | | 3.954+26.7= | | 10y+29-8y=5y+5 | | 6(x-3)=3(x+2)+27 | | 10+200= | | 4-4a=-(1+3a) | | 4w+w-26=19 | | 13u=-42 | | 0.75z=0.25z+12 | | 40=9x+8x | | 12+3(-7x-6)+13x=121 | | 9+4w/10=12/7 | | 3.95x+26.7= | | (x+1)(3x-2)=78x^2 | | z+-73=-4 | | x+.054=-1.802 |

Equations solver categories